Local Norms and the Theory of Planned Behavior: Understanding the Effects of Spatial Proximity on Recycling Intentions and Self-Reported Behavior - Passafaro, Paola; Livi, Stefano; Kosic, Ankica (Frontiers in Psychology, 2019)
This paper aims to deepen the understanding of the role of ‘local norms’ in explaining ecological behaviour within Ajzen’s Theory of Planned Behavior. A longitudinal investigation (overall N=243), focused on households waste recycling, tested the hypothesis that the effects of this type of norms on behavioural intentions varies as a function of the individual’s spatial proximity to the social categories relevant to the social-physical context (in this study: housemates, neighbors, inhabitants of the district or quarter and inhabitants of the city) in which the behaviour takes place. The hypothesis was confirmed and we also showed that the effects of local norms are empirically distinguishable from those of the social norms already considered by the model (i.e. subjective norms). Local norms, also have a direct influence on self-reported recycling behaviour measured one month after intentions. We propose possible theoretical explanations for the results obtained and discuss the implications for applicative purposes.